In-depth analysis of the biomechanical performance of dental implants: square vs. spiral thread designs under chewing conditions / Marsya Athirah Ahmad Kamal ... [et al.] - Ahmad Kamal, Marsya Athirah; Abd Manap, Muhammad Faris; Ismail, Nur Faiqa; Ahmad Ubaidillah, Anas Hakimee; Shaari, Nor Shamimi; Zainudin, Mahfuzah; Shuib, Solehuddin; Ismail, Hazimi (Penerbit UiTM (UiTM Press), 2025)
Dental implants are known as a procedure to replace a missing tooth. The success of dental implants is affected by the amount of force, implant design, and the tension of implant growth surrounding the bone. The purpose of this project is to study the von-Mises stress, total deformation, and contact pressure of biomechanical stress at tooth implants in the lower jaw during chewing simulation by using the finite element method. The models, including the crown, a few screw implants, abutment, and jawbone, were designed in Solidwork with refinement by using Altair Inspire Studio, while the implant simulation has been conducted in ANSYS Workbench. The simulation began by applying three different loadings of 1000N, 1500N and 2000N to the two assembled models of jawbone with different materials of crown and implant. The two constructed models of the jawbone consist of one featuring a square implant and another incorporating a spiral implant. The simulation results indicate that the jawbone model with two different implants experienced deformation and changes in the von-Mises stresses of the implants. It was observed that crowns made of metal or zirconia experienced the lowest stresses, with a value of 4407.5 MPa on the crown during chewing conditions. The mechanical analysis of a square implant under a 1000N load showed a reduction of 896.66 MPa, 1230.1 MPa, and 6.992 mm in von-Mises stress, contact pressure, and total deformation, respectively. The study concludes that square implants under 1000N load demonstrate significantly lower von-Mises stress, contact pressure, and total deformation compared to other implant designs, highlighting their potential effectiveness in reducing biomechanical stress during chewing.